The effect of salbutamol on performance in endurance cyclists - Norris, S. R.; Petersen, S. R.; Jones, R. L. (European Journal of Applied Physiology, 1996)
The effect of salbutamol (S) on cycling performance was examined in 15 highly trained non-asthmatic male cyclists. A double-blind, randomized cross-over design was used with S or placebo (P) administered using a metered-dose inhaler and a spacer device 20 min before each testing session. The S dose was 400 micrograms (four puffs), which is twice the normal therapeutic level. Subjects were habituated to all the laboratory procedures in the week prior to actual data collection. The subjects performed four tests under S and P conditions on separate days over 2 weeks. These included measurement of maximal O2 uptake (VO2max) (cycle ergometry) with assessment of pulmonary function before and after, a submaximal (90% of ventilatory threshold) square-wave work transition from a base of unloaded cycling, a 60-s modified Wingate test, and a simulated 20 km time trial. No significant differences were observed in any of the dependent variables related to aerobic endurance or cycling performance between the S and P conditions. These results support other findings that an acute dose (400 micrograms) of S has no performance-enhancing properties.